Biological activities of sinularin: A literature-based review - Islam, Muhammad Torequl; Hossain, Rajib; Hassan, Shardar Mohammad Hafiz; Salehi, Bahare; Martins, Natália; Sharifi-Rad, Javad; Amarowicz, Ryszard (Cellular and Molecular Biology, 2020)
Sinularin ((9E)-13-hydroxy-4,9,13-trimethyl-17-methylidene-5,15-dioxatricyclo[12.3.1.0(4,6)] octadec-9-en-16-one) is the soft coral-derived hopeful biologically active lead compound. In this review sinularin biological activities are summarized. For that, an up-to-date (from 1980 to Mar 2020) search was made in the PubMed, Science Direct, Web of Science, Scopus, The American Chemical Society, Clinicaltrials.gov, and Google Scholar databases. Data available suggest that sinularin has interesting anti-inflammatory, anticancer, anti-fouling and analgesic potential. The inducible nitric oxide synthase (iNOS), cyclooxigenase (COX)-2, tumor growth factor beta 1 (TGF-Î²1) are the most efficient enzymes for interacting with sinularin due to its anti-inflammatory activity, while phosphoinositol 3-kinase (PI3K), Akt and mechanistic target of rapamycin (mTOR) for its anticancer effect. In conclusion, sinularin seems to be a promissory lead compound in the treatment of inflammation, cancer and neurological disorders.